Strategies for Achieving Gender Justice in Overcoming Multiple Layers of Marginalization Faced by Women Working in the Shallot Industry from an Existentialist Feminist Perspective - Hardiyanti, Marzellina; Natalis, Aga; Claude Geofrey Mahoro, Jean (Jurnal Meta-Yuridis, 2025)
Women who work as shallot sellers are vulnerable to the non-fulfillment of their fundamental labor rights, ranging from the right to receive fair wages to the right to protection from discrimination at work. This study focuses on understanding and analyzing the reasons for the need to protect and fulfill the rights of female shallot harvesters. It examines the reality of female shallot harvesters through an intersectional feminist approach, as outlined by Simone De Beauvoir, and proposes strategies for fulfilling the rights of female shallot harvesters based on gender justice and sustainability. This research employs a non-doctrinal research approach, utilizing a socio-legal perspective that combines primary and secondary data through descriptive-analytical and socio-cultural methods. The results of this research and discussion show that female shallot harvesters need protection and fulfillment of their rights because their welfare and wages are still below the regional minimum wage standard, and their working hours are unlimited as stipulated in Law No. 13 of 2003 concerning Manpower, as well as gender bias issues for female shallot harvesters. The relevance of gender bias and the fulfillment of the rights of female onion peeling workers can be linked to the multiple vulnerabilities faced by women. The position of women, who are often placed after men, is highlighted in Simone de Beauvoir's work The Second Sex with an intersectional approach. This intersectional approach sees the multiple vulnerabilities faced by female shallot peeling workers, not only in terms of unmet decent wage standards but also in terms of gender bias issues. The strategy to fulfill the rights of female shallot sellers needs to be pursued through gender-responsive policies that guarantee the sustainability of their economy in terms of fair wages, appropriate working hours, and employment agreements in accordance with applicable regulations, as well as the right to protection from discrimination at work.